Catholic inheritance under the penal laws in Ireland. Issue 166 (November 2020) - Fitzpatrick, Richard
Abstract: Recent decades have witnessed a continued interest among historians in Ireland's eighteenth-century penal laws. Earlier broad surveys of the laws and their impact have given way to case studies that have highlighted the varied experiences of individual families, with many focusing on the strategies, whether legal or otherwise, that were utilised in attempts to circumvent these restrictions. Despite these advances, however, our understanding of the laws remains incomplete. This is particularly the case in relation to the gavelling clause within the 1704 popery act. This was one of Ireland's most infamous penal laws, yet it remains one of the least studied and least understood set of restrictions against Catholics. It is clear that the restrictions it placed on the sole inheritance of land could be circumvented in certain instances, but how exactly this was achieved without suffering prosecution requires further study. This article will advance our understanding of the gavelling clause through an in-depth examination of the law and its interpretation by Irish courts, which in turn will highlight the avenues that were open to Catholics in their attempts to either neutralise or evade the restrictions and other related legal provisions. This will demonstrate how successful circumvention did not depend on breaking the law per se, but instead relied upon loopholes in the law itself.